CHALLENGES FOR THE UNFCCC IN INDONESIA'S DECENTRALISATION - Salahuddin, Melvin (Indonesia Law Review, 2014)
This article is an examination of the implementation of the United Nations Framework Convention on Climate Change (UNFCCC) as a Multilateral Environmental Agreement (MEA) in Indonesia. It identifies domestic challenges of the Convention in Indonesia’s decentralisation. The implementation of decentralisation policy in 2001 worsens the inherent problems faced by the Convention in Indonesia’s legal system. As a MEA, the Convention contains only general rules for the state parties and no specific legal obligation to reduce emission. The Convention also has legitimacy problems. The Indonesia’s method to transform treaties into domestic legal system is still problematic. These two challenges are worsened by the implementation of decentralisation policy. The national government faces difficulties to drive lower government units to adhere to the Convention rules because they have new authorities that can constraint effort to achieve the goal of the Convention.